2009
DOI: 10.2174/1875398100902010001
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products (AGEs) Damaged IgG, a Target for Circulating Autoantibodies in Patients with Type 1 Diabetes Mellitus

Abstract: Abstract:The role of advanced glycation end products (AGEs)-damaged immunoglobulin G (AGE-IgG) in type 1 diabetes has been investigated in the present study. IgG was isolated from the normal humans and was subjected to in vitro glycation with glucose. The AGEs caused extensive damaged to IgG. The AGE-IgG was found to be highly immunogenic in rabbits as compared to native IgG. The binding characteristics of circulating autoantibodies in type 1 diabetes mellitus (DM) patients against native and AGE-IgG were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…We and others have reported the presence of elevated levels of oxidized protein products (advanced oxidation protein products) such as oxidized plasma protein in patients with various diseases [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Furthermore, ROS modified IgG is highly immunogenic in rabbits, and the antigenic specificity of affinity purified anti-ROS-IgG antibodies and anti-IgG antibodies suggest that induced antibodies are immunogen-specific.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have reported the presence of elevated levels of oxidized protein products (advanced oxidation protein products) such as oxidized plasma protein in patients with various diseases [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Furthermore, ROS modified IgG is highly immunogenic in rabbits, and the antigenic specificity of affinity purified anti-ROS-IgG antibodies and anti-IgG antibodies suggest that induced antibodies are immunogen-specific.…”
Section: Discussionmentioning
confidence: 99%
“…AGEs could be an example of the latter case, although the direct correlation among excessive carbohydrates, AGEs and their autoantibodies has not been verified to date. Previous studies have demonstrated antibody production in response to CML-BSA in diabetic human patients (Shibayama et al, 1999) as well as higher antigenicity of AGE-IgG than IgG (Rasheed et al, 2009).…”
Section: Ajimentioning
confidence: 95%
“…Reports suggest role of AGEs in the activation of inflammatory signalling cascades and in the pathogenesis of diabetic complications [61,77]. Autoimmune response to advanced glycosylation end-products has also been widely reported with B lymphocytes playing a major pathogenic role by the generation of autoantibodies [78].…”
Section: Role Of Glyoxidation Modified Histones In Autoimmune Diseasesmentioning
confidence: 99%